The municipal solid waste management of La Paz (Bolivia): Challenges and opportunities for a sustainable development. Issue 3 (March 2018) - Ferronato, Navarro; Gorritty Portillo, Marcelo Antonio; Guisbert Lizarazu, Edith Gabriela; Torretta, Vincenzo; Bezzi, Marco; Ragazzi, Marco
Municipal solid waste management (MSWM) is considered an important public health, economic and environmental concern, especially in developing countries. This paper introduces the situation of MSWM in La Paz (Bolivia) in 2016, and is based on the Wasteaware indicators and waste flow analysis, useful tools for classifying and comparing waste treatment and management plans among other countries. Taking into account the lack of technology in waste treatment and the presence of a developed informal sector, the paper analyses the main strengths and weak points for implementing a sustainable MSWM. The research conducted revealed that the MSWM of La Paz is not efficient with regard to collection, recycling (8%), financial sustainability, and equity of the service. At the same time, local Government and stakeholders are interested in implementing new MSWM methods for improving the current sanitary state of the city and many efforts were made over the last ten years. In general terms, La Paz could be considered as a good study area for developing plans for waste valorization, becoming an example for a low–middle income developing big city of Latin America. The study provided a few considerations about the affordability of the methodology applied and critically analyzed the case study proposed.